Building with History: Exploring the Relationship between Heritage and Energy in Institutionally Managed Buildings. (July 2014) - Adams, Charlotte; Douglas-Jones, Rachel; Green, Adrian; Lewis, Quentin; Yarrow, Thomas
<x content-type="archive" xml:space="preserve">Abstract</x> Drawing on interdisciplinary research focusing on Durham University estate, we describe how buildings constructed as part of an eighteenth century transition to a high carbon coal-based economy, are used and understood by their current inhabitants. Applied heritage research has tended to focus on the thermal and energetic properties of historic buildings, as distinct from their social meaning and use. A similar separation between the physical building and its social use is inherent in methodologies such as energy audits that constitute key devices through which buildings are institutionally managed. We argue that these perspectives have overlooked how a significant element of energy use arises from the complex practical interactions between people and infrastructure. From this perspective we argue that better outcomes for energy and heritage would result if greater contextual consideration was given to the existing possibilities afforded by historic buildings and their users.